Custos diretos da prematuridade e fatores associados ao nascimento e condições maternas - Melo, Thamires Francelino Mendonça de (2022)
OBJECTIVE: To estimate the direct costs due to hospital care for extremely, moderate, and late preterm newborns, from the perspective of a public hospital in 2018. The second objective was to investigate whether factors associated with birth and maternal conditions explain the costs and length of hospital stay.METHODS: This is a cost-of-illness study, with data extracted from hospital admission authorization forms and medical records of a large public hospital in the Federal District, Brazil. The association of characteristics of preterm newborns and mothers with costs was estimated by linear regression with gamma distribution. In the analysis, the calculation of the parameters of the estimates (B), with a confidence interval of 95% (95%CI), was adopted. The uncertainty parameters were estimated by the 95% confidence interval and standard error using the Bootstrappingmethod, with 1,000 samples. Deterministic sensitivity analysis was performed, considering lower and upper limits of 95%CI in the variation of each cost component.RESULTS: A total of 147 preterm newborns were included. We verified an average cost of BRL 1,120 for late preterm infants, BRL 6,688 for moderate preterm infants, and BRL 17,395 for extremely preterm infants. We also observed that factors associated with the cost were gestational age (B = -123.00; 95%CI: -241.60 to -4.50); hospitalization in neonatal ICU (B = 6,932.70; 95%CI: 5,309.40–8,556.00), and number of prenatal consultations (B = -227.70; 95%CI: -403.30 to -52.00).CONCLUSIONS: We found a considerable direct cost resulting from the care of preterm newborns. Extreme prematurity showed a cost 15.5 times higher than late prematurity. We also verified that a greater number of prenatal consultations and gestational age were associated with a reduction in the costs of prematurity.